THE IMPACT OF COVID-19 ON CONSUMERS’ ONLINE SHOPPING BEHAVIOR AN EXPLORATORY STUDY OF THE OPINIONS OF A SAMPLE OF CONSUMERS IN KURDISTAN REGION–IRAQ - ARABI, AYA SAADOON (Journal of Duhok University, 2023)
Due to the increase in using the internet, online shopping has become very suitable for many consumers. Moreover, owing to COVID-19, online shopping became more appealing, considering the lockdown and health restrictions. This research’s purpose is to identify the effect of COVID-19 on consumers’ online shopping behavior, the research has two main hypotheses which are, there is a significant and positive statical correlation between COVID-19 and consumers’ online shopping behavior, and COVID-19 has a significant effect on consumers’ online shopping behavior. In this research the independent variable is COVID-19 and the dependent variable is online shopping which has four factors (convenience, time-saving, web design & literacy, and security). The research studied a random sample of consumers in Kurdistan region – Iraq, (120) electronic forms of the research questionnaire were distributed to the respondents, and (108) forms were returned and valid which represent a percentage of (90 %) of the distributed questionnaire. The research revealed that there is a significant and positive correlation between three of the online factors which are (time-saving, web design & literacy, and security) and COVID-19, while the correlation between the first online shopping factor (convenience) and COVID-19 was insignificant, also there is a significant effect of COVID-19 on online shopping. The research suggests since consumers increased their dependence on online shopping during the pandemic in the percentage of (22.5 %), the markets and businesses in Kurdistan region – Iraq should consider enhancement in their online services and delivery timing and packaging in order to offer and present the best service to their customers and keep in competition in the markets